Analysis Of Officers Performance Of Medical Recording In Puskesmas Anak Setatah Rangsang Barat District Meranti Regency 2022 : Analisis Kinerja Petugas Rekam Medis di Puskesmas Anak Setatah Kecamatan Rangsang Barat Kabupaten Meranti Tahun 2022 - Nurul Suci Rahayu; Henny Maria Ulfa; Yessi Harnani; Nur'aina Basir; Raviola Raviola (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Performance is the result of work achieved by workers or employees in quality and quantity in accordance with their duties and responsibilities. The problem found is that there is still a lack of ability and expertise of medical record officers in the medical record file storage section, and there is still a lack of infrastructure in the medical record room. The purpose of this study in general is to determine the performance of medical record officers. This study uses qualitative methods of observation, in-depth interviews. The research location was conducted at the Medical Record Section of the Setatah Children's Health Center, Rangsang Barat District, Meranti Regency in February-April 2022. The subjects in the study consisted of the head of the puskesmas, head of medical records, medical record officer, registration officer and TU of the puskesmas. The data processing technique uses source triangulation, method triangulation and data triangulation. Data analysis in this study consisted of data reduction, data presentation and verification/conclusion. The results of the study revealed that there were still some medical record files that were incorrectly stored and the provision of medical record files was found for more than 10 minutes, there had been no training for medical record officers, the motivation given by superiors was only in the form of directions not given rewards, lack of infrastructure such as computers. which supports the application and the lack of a medical record room. For this reason, officers are expected to improve the abilities and expertise of officers, participate in training, provide increased motivation to officers and can add supporting facilities so that they can support better officer performance.